I have the following system. $\vec{x^{'}}(t)=\begin{pmatrix}4&-2\\8&-4 \end{pmatrix} \vec{x}+ \begin{pmatrix}t^{-3}\\-t^{-2}\end{pmatrix}$

I get $\lambda=0$ and the eigenvector of $$4x_1=2x_2 \implies \begin{pmatrix} 1\\2 \end{pmatrix}$$

Next I solved $$\begin{pmatrix}4&-2\\8&-4\end{pmatrix}\begin{pmatrix}\vec{o_1}\\ \vec{o_2} \end{pmatrix}=\begin{pmatrix}1\\2 \end{pmatrix} \implies \vec{o_1}=\dfrac{1+2\vec{o_2}}{4}$$

So can choose a eigenvector of $\begin{pmatrix} 0\\\frac{-1}{2} \end{pmatrix}$

Therefore, since $\lambda=0$ the fundamental matrix will be just the eigenvectors coupled together that is $$\phi(t)=\begin{pmatrix} 1&t\\2&2t-\frac{1}{2} \end{pmatrix}\implies \phi^{-1}(t)=\begin{pmatrix}1-4t&2t\\4&-2\end{pmatrix}$$

I multiply this matrix by $g(t)$ to get $$\begin{pmatrix}t^{-3}-4t^{-2}-2t^{-1}\\4t^{-3}+2t^{-2}\end{pmatrix}$$

Taking the integral gives me $$\begin{pmatrix} \frac{-1}{2}t^{-2}+4t^{-1}-2\ln t\\-2t^{-2}-2t^{-1} \end{pmatrix}$$

I multiply by $\phi(t)$ to get $\begin{pmatrix}1&t\\2&2t-\frac{1}{2}\end{pmatrix}\begin{pmatrix} \frac{-1}{2}t^{-2}+4t^{-1}-2\ln t\\-2t^{-2}-2t^{-1} \end{pmatrix}=\begin{pmatrix}-\frac{1}{2}t^{-2}-2\ln t+2t^{-1} -2\\-4\ln t+5t^{-1}-4 \end{pmatrix}$

Why cant I get these right...

Therefore all that is left is to multiply by $\phi$ and add the homogenous solution which is simply $\begin{pmatrix}1\\2 \end{pmatrix}c_1+c_2\bigg[t\begin{pmatrix}1\\2\end{pmatrix}+\begin{pmatrix}\frac{1}{4}\\0 \end{pmatrix}\bigg]+ x_p$ where $x_p$ is the particular solution. In the book they got something way off that is $$\begin{pmatrix}1\\2 \end{pmatrix}c_1+c_2\bigg[\begin{pmatrix}1\\2\end{pmatrix}t-\frac{1}{2}\begin{pmatrix}0\\1 \end{pmatrix}\bigg]-2\begin{pmatrix}1\\2 \end{pmatrix} \ln t+\begin{pmatrix}2\\5 \end{pmatrix}t^{-1}-\begin{pmatrix}\frac{1}{2}\\0 \end{pmatrix}t^{-2}$$

  • $\begingroup$ @Amzoti I posted my work can you tell me where I'm going wrong in my procedure? $\endgroup$ – adam Apr 24 '14 at 2:30


$$\vec{x^{'}}(t)=\begin{pmatrix}4&-2\\8&-4 \end{pmatrix} \vec{x}+ \begin{pmatrix}t^{-3}\\-t^{-2}\end{pmatrix}$$

We have as eigenvalues and eigenvectors:

$$\lambda_{1,2} = 0, v_1 = (1,2), v_2 = \left(\dfrac{1}{4},0\right)$$

Update 1: Note that eigenvectors are not unique and your book chose $v_2 = \left( 0, -\dfrac{1}{2}\right)$.

From this, we can write the general solution as:

$$x(t) = e^{0t}\left(c_1 \begin{bmatrix} 1\\2 \end{bmatrix} + c_2\left(\begin{bmatrix} 0\\-\frac{1}{2} \end{bmatrix} + t\begin{bmatrix} 1\\2 \end{bmatrix} \right) \right) = \begin{bmatrix} c_1 + c_2 t \\2c_1 + c_2\left(-\frac{1}{2} +2 t \right)\end{bmatrix}$$

This means we have:

$$\phi(t) = \begin{bmatrix} 1 & t \\2 & -\frac{1}{2} + 2 t \end{bmatrix}$$

Now, to find the exponential, just take:

$$e^{At} = \phi(t) \phi^{-1}(0) = \begin{bmatrix} 1 + 4 t & -2 t \\ 8 t & 1 - 4 t \end{bmatrix}$$

Do you see where your $\phi(t)$ went astray? Recall, we have a repeated eigenvalue with a generalized eigenvector!

Update 2

Recall, we have:

$$X(t) = e^{At}X_0 + \int_{t_0}^t e^{A(t-s)}F(s)~ds$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.